2015
DOI: 10.1007/s11356-015-4653-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoranthene on the fitness-related traits and antioxidative defense in Lymantria dispar L.

Abstract: This study aimed to examine the effects of ubiquitous polycyclic aromatic hydrocarbon fluoranthene, supplemented to an artificial diet, on the fitness-related traits and activity of midgut antioxidative enzymes-superoxide dismutase (SOD) and catalase (CAT), and expression of their isoforms in the fifth-instar gypsy moth Lymantria dispar L. Prolonged duration of development and reduced weight and relative growth rate were recorded in larvae reared on the diets supplemented with different concentrations of fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The effects of fluoranthene have been studied in aquatic organisms, but examinations related to the impact on terrestrial insect species are scarce (Bach et al, 2005;Schuller et al, 2007;Baas et al, 2010). The acute toxicity in Daphnia magna following exposure to fluoranthene and UV light is thought to be due to production of singlet oxygen or free radicals (Wernersson and Dave, 1998), while induction of detoxifying enzymes in Aedes aegipty larvae (Poupardin et al, 2008) and increased activity of antioxidative enzymes in L. dispar larvae (Mrdaković et al, 2015) were shown to be responses to fluoranthene exposure. In the present study significant changes of antioxidative enzyme activity were for the first time recorded in whole midguts and midgut tissues (without the peritrophic membrane) of L. dispar and E. chrysorrhoea larvae exposed to dietary fluoranthene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of fluoranthene have been studied in aquatic organisms, but examinations related to the impact on terrestrial insect species are scarce (Bach et al, 2005;Schuller et al, 2007;Baas et al, 2010). The acute toxicity in Daphnia magna following exposure to fluoranthene and UV light is thought to be due to production of singlet oxygen or free radicals (Wernersson and Dave, 1998), while induction of detoxifying enzymes in Aedes aegipty larvae (Poupardin et al, 2008) and increased activity of antioxidative enzymes in L. dispar larvae (Mrdaković et al, 2015) were shown to be responses to fluoranthene exposure. In the present study significant changes of antioxidative enzyme activity were for the first time recorded in whole midguts and midgut tissues (without the peritrophic membrane) of L. dispar and E. chrysorrhoea larvae exposed to dietary fluoranthene.…”
Section: Discussionmentioning
confidence: 99%
“…Alfani et al, 2001;Tian et al, 2008). In addition, our previous research on the effects of a wide range fluoranthene concentrations revealed the most prominent influence of the chosen concentrations (6.7 and 67 ng of fluoranthene) on larval mass, relative growth rate, and enzyme activities in gypsy moths (Mrdaković et al, 2015). The food supplemented with fluoranthene was prepared by mixing the HWG diet with fluoranthene dissolved in reagent-grade acetone.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…This disruption of larval growth, which is apparently inconsistent with the applied B[a]P concentration, seems to be the characteristic response for this type of compound in L. dispar. Previous investigation of B[a]P and fluoranthene influence on L. dispar larval development and growth showed that mainly a lower concentration of these PAHs caused the greatest harm to larval fitness [15,40]. It is possible that the B[a] P mechanism of action resembles the class of compounds called endocrine disruptors (EDCs), which elicit reverse responses of different parameters as the concentration of disruptors increases, resulting in an U-shaped or inverted U-shaped curve [41].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies of the physiological responses of L. dispar to various types of stressors, we observed significant changes in biochemical parameters, which points to their potential use as indicators of adverse environmental changes [12,13]. Many investigations have shown the negative effects of PAHs on insect development and reproduction [14,15]. L. dispar is an insect species that is a very suitable model system for this type of research, considering the uncomplicated manipulation of individuals in laboratory conditions, their short generation time, precisely defined developmental stages and well-known physiological processes.…”
Section: Introductionmentioning
confidence: 87%
“…The aim of this study was to examine the effects of EO and mesoporous nanosilica carrier SBA-15 loaded with EO on the antioxidative defenses, specifically superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), and glutathione reductase (GR), in E. chrysorrhoea larvae. Lepidopteran larvae rely on these antioxidative enzymes and ascorbate peroxidase (APOX), as well as on nonenzymatic cellular antioxidants, glutathione (GSH), ascorbic acid, and others to counteract the free-radical cascade of oxygen (Perić-Mataruga et al, 1997Krishnan and Kodrík, 2006;Jena et al, 2013;Mirčić et al, 2013;Mrdaković et al, 2015;Renault et al, 2016). The superoxide radicals generated under oxidative stress are rapidly dismutated to hydrogen peroxide by SOD.…”
Section: Introductionmentioning
confidence: 99%